Implementasi Program Siap Akta Kelahiran Dan Kartu Identitas Anak (Program Si Adik) Pada Tingkat Sekolah Dasar Di Dinas Kependudukan Dan Pencatatan Sipil Kota Binjai - Cindyayudiamatra Cindy; Februati Trimurni (UIR Press, 2024)
The government always strives to improve the quality of public services provided to the community, one of which is administrative services. Regulation of the Minister of Home Affairs (Permendagri) Number 19 of 2018 concerning Improving the Quality of Population Administration Services in the Population and Civil Registration Office of the Regency / City quickly and precisely through integrated services and / or pick up the ball for the fulfillment of ownership of resident identity. Therefore, the Binjai City Population and Civil Accounting Service issued a program, namely the Ready for Birth Certificates and Child Identity Card (SI ADIK Program) in realizing the improvement of the quality of population administration services through integrated services. The method used in this study is a descriptive method with a qualitative approach. The data collection techniques are interviews, observations and documentation. The results showed that the implementation of the Ready for Birth Certificate and Child Identity Card Program (SI ADIK program) at the Binjai City Population and Civil Registration Service was still not optimal. This can be seen from the need to increase socialization to the target parties of the program, then increase existing resources both in terms of quantity and quality. It requires the commitment and readiness of implementers of effective programs and mechanisms.